To convert the quadratic from vertex form \( y = 2(x - 5)^2 - 10 \) to standard form, we need to expand the equation.
-
Start with the vertex form: \[ y = 2(x - 5)^2 - 10 \]
-
Expand \( (x - 5)^2 \): \[ (x - 5)^2 = x^2 - 10x + 25 \]
-
Substitute this back into the equation: \[ y = 2(x^2 - 10x + 25) - 10 \]
-
Distribute the \( 2 \): \[ y = 2x^2 - 20x + 50 - 10 \]
-
Combine like terms: \[ y = 2x^2 - 20x + 40 \]
Now we have it in the standard form \( y = ax^2 + bx + c \), where \( a = 2 \), \( b = -20 \), and \( c = 40 \).
Thus, the standard form of the quadratic is: \[ y = 2x^2 - 20x + 40 \]
So the completed equation is: The standard form of the quadratic is \(y = 2x^2 + (-20)x + 40\).